Leadership Soft Skills and Organizational Climate Affecting The Knowledge Management of Health Personnel in Yasothon Provincial Public Health Office - Meetham, Nakamon; Bouphan, Prachak; Prasit, Nakarin (Journal of The Royal Thai Army Nurses, 2025)
This cross-sectional descriptive research aimed to study leadership soft skills and organizational climate affecting the knowledge management of health personnel in Yasothon provincial public health office, Thailand. The Sample size was health personnel in Yasothon provincial public health office, 143 people. The quantitative data was collected by using questionnaires and collecting qualitative data was collected by using In-Depth interview guidelines that examined and verified by the three experts for content validity. The item objective congruence (IOC) was more than 0.50 for each items and Cronbach’s Alpha Coefficient was 0.98. Data analysis was performed by using descriptive and inferential statistics, including Pearson correlation coefficient and stepwise multiple linear regression. The qualitative data, content analysis was performed. The results showed that the overall level of leadership soft skills, organizational climate and knowledge management were at a high level. Four variables composed of organizational climate performance standards, leadership soft skills planning and organization, organizational climate risk, and leadership soft skills teaching affected and could jointly predict the knowledge management of health personnel in Yasothon provincial public health office at 80.2%